Impact of surgery on survival in breast cancer with bone metastases only: a SEER database retrospective analysis - Pai Peng; Jiang-Yuan Chen; Yun-Tao Han; Xin Chen; Hong-Yuan Li; Chao-Hua Hu; Jin-Li Wang (BMC Surgery, 2021)
Abstract Background It was controversial to operate on the primary site of breast cancer (BC) with bone metastasis only. We investigated the impact of surgery on BC patients with bone metastases via a SEER database retrospective analysis. Methods A total of 2917 BC cases with bone metastasis, first diagnosed between 2010 and 2015 in the Surveillance, Epidemiology, and Results Database (SEER) of National Cancer Institute were selected. We assessed the effect of different surgical procedures on survival and prognosis. Results Compared with the non-surgical group, the primary tumor surgical group showed longer median survival time (χ2 = 146.023, P < 0.001), and the breast-conserving subgroup showed the highest median survival time of 70 months (χ2 = 157.117, P < 0.001). Compared with the non-surgery group, the median overall survival (OS) of primary surgery group was longer (HR = 0.525, 95%CI = 0.467–0.590, P < 0.001), and the breast-conserving subgroup showed the longest median operative OS (HR = 0.394, 95%CI = 0.325–0.478, P < 0.001). Conclusion This study showed that primary surgery could improve the median survival time and OS of BC patients with bone metastasis. Moreover, under the condition of low tumor burden, breast conserving surgery was a better choice.